Bantuan Zakat Pendidikan Kepada Golongan Asnaf: Kajian Perbandingan Antara Negeri Sembilan Dan Negeri Selangor - Siti Martiah Anwa; Mohd Faez Abu Bakar; Azman Ab. Rahman; Nor Asiah Yaakub (Universiti Sains Islam Malaysia, 2024)
Zakat institution is responsible in distributing the zakat to eight asnaf as has been decreed in the Quran which are to the poor, needy, muallaf, fi sabilillah, ibnu sabil, gharimin, riqab and amil. The distribution of zakat is in various forms and schemes like educational assistance, cost living, health assistance, human capital development, entrepreneurship, economic assistance and natural disasters aid. However this paper is focussing more on the educational aids to asnaf. Therefore, this paper is to examine the scheme and educational aids given to the asnaf especially in Negeri Sembilan and Negeri Selangor. Furthermore, this paper will analyse the scheme and educational aids, whether there is a significant differences between the scheme and educational aids in both states which affected in the development of education and later helps in strengthening the economy of the ummah.This research applied the quantitative research methodology which is field study using interviews methods and qualitative using the documentation research in the form of deductive and inductive methods. The finding of the research indicated that the educational aids in Negeri Sembilan is given also to the asnaf ar-riqab instead of asnaf poor and needy like in the state of Selangor. However, it does not impair the main objectivity of the aids which is to give equal opportunity and continuous education until successful in their study. It is hoped that this research will gives a better overview and understanding to the society on the types of educational aids offered to the asnaf and whom are qualified to such assistance. Educational aids is very important to help the asnaf to get a better education and career in the future which will also contribute to the empowerment of the economy of ummah.